Assessment of iridoid profiles in the growth period of aerial parts of Pseudolysimachion rotundum var. subintegrum and their antioxidant and MUC5AC inhibitory potential - Soobin Song; Doo-Young Kim; Seon Min Oh; So-Yeun Woo; Il-joo Kim; Mun-Ock Kim; Ji-Yoon Park; Namho Kim; Hae-Young Kim; Juhee Lee; Sang Yoon Kim; Bang Yeon Hwang; et al. (Applied Biological Chemistry)
Abstract YPL-001 is a drug substance of Pseudolysimachion rotundum var. subintegrum and has been reported to be a potent COPD inhibitor. For the first time, this study demonstrated a correlation among the iridoid constituents, antioxidants, and MUC5AC inhibition activities in P. rotundum during different growth stages (5 to 11 weeks). Single-factor extraction was used to optimize the plant extraction conditions to maximize the major iridoid constituents (70% ethanol, 40 °C, 1 h); isolated metabolites 1–6 were identified using nuclear magnetic resonance spectroscopy (NMR) and mass spectrometry (MS). The contents of each metabolite and antioxidant/MUC5AC inhibition effects were markedly changed according to the growth stages, especially for catalposide (2, 5.97 → 10.99 mg/g, 1.8-fold) and isovanillyl catapol (5, 4.42 → 20.00 mg/g, 4.5-fold), which were the predominant substances in August. Our results indicated that YPL-001 could potentially contribute to enhancing the P. rotundum value in accumulated iridoids at the growth stage and the biological effect aspects to develop industrial medicinal crops.